Cecilia M. Shore, Individual differences in language development. SAGE, Thousand Oaks, CA, 1995; 148 pp. - Karina Hess Zimmermann (Nueva Revista de Filología Hispánica, 1997)
Se reseñó el libro: Individual differences in language development.